Obtaining wild sunflower (Helianthus annuus L.) plants for bioassays with herbicides - Cisneros-López, Ma. Eugenia (2024)
Introduction. The wild sunflower or polocote (Helianthus annuus L.) is the main annual weed in the cultivation of sorghum and corn in northern Tamaulipas, Mexico. To date, there is little information about this species to carry out bioassays with herbicides. Objective. Establish a methodology for obtaining polocote seedlings for bioassays with herbicides, from seed to multiplication in the nursery. Materials and methods. The polocote seed was collected in January 2023, within the National Institute of Forestry, Agriculture and Livestock Research (INIFAP) Experimental Field, in Río Bravo, Tamaulipas. Afterwards, the initial germination test was carried out on filter paper and viability with tetrazolium. Latency was confirmed due to low germination (12 %) and high viability (86 %). Twelve treatments were used to break dormancy using ethanol (70 %) and water (75, 25). As a control only water were used. The treatments were applied at temperatures of 5 °C and 20 °C, on filter paper, cotton, and peat moss in Petri dishes for seven days. Subsequently, they were kept at a temperature of ±25 °C. With the previous results, the nursery phase was established with four schemes with pre-germinated seed transplantation and two with direct sowing. Results. The best treatment to break dormancy was immersion in water at 5 °C for seven days on cotton, with 73 % germination. The best methods to obtain plants were trays with seedlings and transplanting into black open-air pots, with 75 % and 50 % survival, respectively. Shade inhibited plant growth. Direct sowing, with or without seed prehydration, was unfavorable for germination and emergence. Conclusion. Obtaining wild sunflower seedlings was higher when the seed was subjected to water pre-treatment and subsequent transplanting into trays or open-air bags.